Le séisme de Pisco du 15 août 2007 : entre urgence et reconstruction - Robert D'Ercole; Jérôme Chandes; Hugo Perfettini; Laurence Audin (EchoGéo)
More than three months have passed since the earthquake, on the Peruvian coast, 200 km south of Lima, killed more than 500 people. The number of casualties is small in comparison with the damage recorded, but the number of homeless people is very high. While the event is almost forgotten at the international level, tens of thousands of people are still living in precarious conditions in the temporary shelters provided by the emergency, until begins the reconstruction process. In this context, the objective of this article is to make an initial assessment of the characteristics of the earthquake and its effects, the management of the crisis and the current situation that oscillates between relief and reconstruction.